Quản lí bồi dưỡng năng lực số cho giảng viên các Học viện Công an nhân dân trong bối cảnh chuyển đổi số: Một phân tích tổng quan - Nguyễn Phạm, Mạnh Hùng; Bùi Minh Đức, Bùi Minh Đức; Nguyễn Thị Minh Nguyệt, Nguyễn Thị Minh Nguyệt (Tạp chí Giáo dục, 2026)
In the context of digital transformation, digital competence has become an important component of lecturers’ professional competence. This article employs a scoping review approach to systematize 31 domestic and international studies on digital competence, digital competence development, and the management of digital competence development for lecturers, with attention to the specific context of the People’s Public Security Academies. The review indicates that lecturers’ digital competence is a complex professional competence comprising technological competence, digital pedagogy, learning material design, digital assessment, digital ethics, information security, data competence, and professional development. The findings also show that existing studies have mainly focused on concepts, competence frameworks, and training content, while the management of digital competence development as a cycle, including standard identification, needs assessment, implementation, condition assurance, evaluation, and improvement, has not been sufficiently examined. In the context of the People’s Public Security Academies, political, legal, professional, disciplinary, information security, and data management requirements create a need to develop a management model for digital competence development that is appropriate to the specific characteristics of the sector.